Optimizing vancomycin dosage regimens in relation to high-flux haemodialysis. (11th September 2018) - Hui, Katrina; Patel, Kashyap; Nalder, Michelle; Nelson, Craig; Buising, Kirsty; Pedagogos, Eugenie; Kong, David C M; Kirkpatrick, Carl M J
Abstract: Objectives: To develop a population pharmacokinetic (PK) model for vancomycin in adults receiving high-flux haemodialysis (HFHD) in an effort to optimize vancomycin dosing in this population. Methods: A population PK model using NONMEM was developed using retrospective data collected from 48 vancomycin courses administered to patients ( n = 37) receiving HFHD. Fixed-dose [1.5 g loading dose (LD), 1 g maintenance dose (MD)], literature-adapted weight-based (WBL; 20 mg/kg LD, 10 mg/kg MD) and hospital-adapted weight-based (WBH; 25–30 mg/kg LD, 20–25 mg/kg MD) dosage regimens were then simulated using the Monte Carlo method. The PTA was an AUC24 /MIC ≥400 with success being a PTA ≥90%. Results: The data were best described using a two-compartment model. It was observed that fixed-dose and WBL dosage regimens resulted in a PTA ≤90% for most days. The WBH dosing achieved a PTA ≥90% on most days, but there were supratherapeutic concentrations with repeated dosing of vancomycin. If HFHD was delayed by 48–72 h after the LD, the PTA would fall below 90%. A dose-optimized regimen was developed: 30 mg/kg LD and 10 mg/kg MD given on HFHD days. An additional dose of 500 mg or 1 g was administered 24 h after the LD if HFHD occurred 48–72 h post-LD. This dose-optimized regimen afforded a PTA ≥90% on all days of therapy and achieved clinically acceptable pre-haemodialysis concentrations. Conclusions: Current vancomycin dosage regimens used clinically do not achieve a PTA ≥90% for most days of therapy for people receiving HFHD. A dose-optimized regimen was developed, which could be implemented in clinical practice.